The Tamarack murders [large type] : a Bo Tully mystery - McManus, Patrick F. (McManus, Patrick F. Sheriff Bo Tully mystery., 2014)
After Sheriff Bo Tully witnesses a murder while pursuing a bank robber, he is thrust into an investigation that will test his crime-solving skills.